Effects of salvianolic acid B on glycometabolism and lipid metabolism in rodents: Meta-analysis - Bohan Lv; Tian An; Tingye Wang; Xueli Bao; Juan Lian; Yanxiang Wu; Yuanyuan Hu; Jiajian Zhu; Chunyan Zheng; Xuehong Hu; Sihua Gao; Guangjian Jiang (World Scientific Publishing, 2020)
Danshen (Salvia miltiorrhiza) is a herb which has been widely used in China. Salvianolic acid B (SalB) is an aqueous bioactive component derived from Danshen. Here, we aimed to estimate the effect of SalB on glycometabolism and lipid metabolism in rats and mice. We searched four databases until November 2020. The outcome measures were fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDLc), and low-density lipoprotein cholesterol (LDLc). Twenty-four studies involving 547 animals were included. The meta-analysis showed effects of SalB on decreasing the level of FBG, TC, TG, LDLc, and increasing the level of HDLc compared with the control group. In conclusion, the result showed that SalB may regulate the glycometabolism and lipid metabolism in rats or mice, and may be a potential agent for treating metabolic diseases such as diabetes and hyperlipidemia.